Tissue Plasminogen Activator in Nervous System Function and Dysfunction - Strickland, Sidney (Thrombosis and Haemostasis, 2001)
The extracellular protease tissue plasminogen activator (tPA) has been implicated in various normal and pathological situations in the mammalian nervous system. The availability of (i) transgenic and knock-out mice in which the expression level of tPA can be widely varied, (ii) in vivo models for studying function and disease, and (iii) culture models for examining cell behavior, has allowed a detailed evaluation of many of these proposed functions. This chapter summarizes the current state of knowledge of possible roles for the tPA/plasminogen system in neuronal function and dysfunction.
Keywords: tPA; plasminogen; fibrin; laminin; nervous system